2006
DOI: 10.1111/j.1365-2125.2006.02707.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of voriconazole on the pharmacokinetics and pharmacodynamics of zolpidem in healthy subjects

Abstract: AimsTo assess the effect of voriconazole on the pharmacokinetics and pharmacodynamics of zolpidem. MethodsIn a randomized cross-over study with two phases, 10 healthy subjects ingested 10 mg of zolpidem with or without oral voriconazole pretreatment. The concentrations of zolpidem were measured in plasma up to 24 h and pharmacodynamic variables were monitored for 12 h. ResultsVoriconazole increased the peak plasma concentration of zolpidem by 1.23-fold [ P < 0.05; 90% confidence interval (CI) 1.05, 1.45] and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…It is plausible to assume that the observed pharmacokinetic changes are due to a marked decrease in the first-pass metabolism and plasma clearance of oxycodone because both the C max , AUC 0-∞ and t 1/2 of oxycodone were greatly increased by voriconazole, and these changes were accompanied by drastic changes in the metabolite-to-oxycodone ratios. Previous human studies have shown that voriconazole alters the pharmacokinetics of several drugs metabolized by CYP3A, including oral hypnotics [23][24][25] and opioids [26][27][28]. Voriconazole decreases the clearance of alfentanil by 83% [26] and that of fentanyl by 23% [27], and increases the AUC 0-24 of R-methadone by 47% [28].…”
Section: Discussionmentioning
confidence: 99%
“…It is plausible to assume that the observed pharmacokinetic changes are due to a marked decrease in the first-pass metabolism and plasma clearance of oxycodone because both the C max , AUC 0-∞ and t 1/2 of oxycodone were greatly increased by voriconazole, and these changes were accompanied by drastic changes in the metabolite-to-oxycodone ratios. Previous human studies have shown that voriconazole alters the pharmacokinetics of several drugs metabolized by CYP3A, including oral hypnotics [23][24][25] and opioids [26][27][28]. Voriconazole decreases the clearance of alfentanil by 83% [26] and that of fentanyl by 23% [27], and increases the AUC 0-24 of R-methadone by 47% [28].…”
Section: Discussionmentioning
confidence: 99%
“…Ci Phenytoin (CYP450 induction) 85,93 Significantly reduced increase voriconazole maintenance dose St. John's wort (CYP450 inducer) 103 Significantly reduced Ci Oral contraceptives containing ethinyl estradiol and norethindrone (CYP2C19 inhibition) 57 increased…”
Section: CImentioning
confidence: 99%
“…Clinically important drug interactions with zolpidem have been extensively reviewed. Drugs that inhibit or induce CYP isoenzymes may result in drug interactions with zolpidem (Swainston and Keatin 2005;Von Moltke et al 1999;Farkas et al 2009;Saari et al 2006;Cysneiros et al 2007;Villikka et al 1997).…”
Section: Introductionmentioning
confidence: 99%